26.9k views
4 votes
Can you rewrite a sine as a cosine function and vice versa when describing a general sinusoidal graph? Explain.

User Vishnu M C
by
5.4k points

1 Answer

2 votes

Answer:


sin(x+(\pi)/(2))=cos(x)


cos(x-(\pi)/(2))=sin(x)

Explanation:

* Lets explain how to solve the problem

- We can write a sine as a cosine by translate the sine function to the

left by
(\pi)/(2)

-
sin(x+(\pi)/(2))=cos(x)

∵ The value of sin(0 + π/2) = 1

∵ cos(0) = 1

∴ sin(0 + π/2) = cos(0)

∴ If sin(x) translated to the left by
(\pi)/(2), then it will be

cos(x)


sin(x+(\pi)/(2))=cos(x)

- Vice versa

- We can write a cosine as a sine by translate the cosine function to

the right by
(\pi)/(2)

-
cos(x-(\pi)/(2))=sin(x)

∵ The value of cos(0 - π/2) = 0

∵ sin(0) = 0

∴ cos(0 - π/2) = sin(0)

∴ If cos(x) translated to the right by
(\pi)/(2), then it will be

sin(x)


cos(x-(\pi)/(2))=sin(x))

- Look to the attached graphs for more understand

Can you rewrite a sine as a cosine function and vice versa when describing a general-example-1
Can you rewrite a sine as a cosine function and vice versa when describing a general-example-2
User Nazarii Moshenskyi
by
5.8k points